Accelerating the Adaptability of Online Learning at Course and Training Institutions in the Era of the Covid-19 Pandemic - Wiwin Herwina; Islahudin Islahudin (Journal of Nonformal Education, 2023)
The COVID-19 pandemic that has not ended requires non-formal educational institutions to adapt to distance learning or online learning so that educational practices are still carried out. This research aims to explore the adaptation of online learning in the course and training institutions in the era of the COVID-19 pandemic. This research uses descriptive methods with a qualitative approach. Data collection is done through observation, structured interviews, and documentation studies. The research findings show that the adaptation of online learning in Tasikmalaya city courses and training institutions during the COVID-19 pandemic is carried out in two ways, namely, online and offline learning. Online learning uses available learning technologies such as zoom, Google meet, internal websites for meetings, and Google classroom for assignments. In comparison, offline learning (face-to-face) is done with many provisions (for example: requiring tutors and learning residents to follow health protocols, limiting the number of learning residents present, reducing lesson hours, dividing classes into two study rooms). Blended learning is considered quite effective by institution managers in providing community services to maintain the quality of graduates during the pandemic Covid -19.